The effects of autonomy support in physical education classes [Efectos del soporte de autonomía en clases de educación física]. - Juan Antonio Moreno-Murcia; Francisco Sánchez-Latorre (Ramón Cantó Alcaraz, 2016)
The aim of this study was to analyze the behavioral, affective and cognitive effects that an intervention based on autonomy support has in physical education classes. The sample consisted of 145 students aged between 10 and 12 (M = 10.37; SD = .68). The experimental group (n = 91) consisted of four groups (two fifth grade and two sixth) and control group (n = 54) for a fifth year and one sixth of primary education. Autonomy support, the basic psychological needs, intrinsic motivation, importance attributed to physical education and the rate of regular physical activity were measured. Before the study began, the instructor involved participated in a workshop on autonomy support. During the same he was taught the concepts advocated by the SDT motivation and behavior training to facilitate greater levels of autonomy support, in addition to lowering the driver style statements in their classes. After the intervention (21 programmed physical education classes in four months), the results showed that the experimental group experienced significant increases in autonomy, intrinsic motivation, importance of physical education, intention to do sport and regular physical activity. Autonomy support in students had positive cognitive, affective and behavioral consequences.